Effect of different types of face masks on the ventilatory and cardiovascular response to maximal-intensity exercise - Rojo-Tirado, Miguel A.; Benítez-Muñoz, José A.; Alcocer-Ayuga, María; Alfaro-Magallanes, Víctor M.; Romero-Parra, Nuria; Peinado, Ana B.; Rael, Beatriz; Castro, Eliane A. [UNESP]; Benito, Pedro J. (MDPI, 2021)
The development of new models of face masks makes it necessary to compare their impact on exercise. Therefore, the aim of this work was to compare the cardiopulmonary response to a maximal incremental test, perceived ventilation, exertion, and comfort using FFP2 or Emotion masks in young female athletes. Thirteen healthy sportswomen (22.08 ± 1.75 years) performed a spirometry, and a graded exercise test on a treadmill, with a JAEGER® Vyntus CPX gas analyzer using an ergospirometry mask (ErgoMask) or wearing the FFP2 or the Emotion mask below the ErgoMask, randomized on 3 consecutive days. Also, menstrual cycle status was monitored to avoid possible intrasubject alterations. The results showed lower values for the ErgoMask+FFP2, compared to ErgoMask or ErgoMask+Emotion, in forced vital capacity (3.8 ± 0.2, 4.5 ± 0.2 and 4.1 ± 0.1 l, respectively); forced expiratory volume in 1 s (3.3 ± 0.2, 3.7 ± 0.2 and 3.5 ± 0.1 l); ventilation (40.9 ± 1.5, 50.6 ± 1.5 and 46.9 ± 1.2 l/min); breathing frequency (32.7 ± 1.1, 37.4 ± 1.1 and 35.3 ± 1.4 bpm); VE/VO2 (30.5 ± 0.7, 34.6 ± 0.9 and 33.6 ± 0.7); VE/VCO2 (32.2 ± 0.6, 36.2 ± 0.9 and 34.4 ± 0.7) and time to exhaustion (492.4 ± 9.7, 521.7 ± 8.6 and 520.1 ± 9.5 s) and higher values in inspiratory time (0.99 ± 0.04, 0.82 ± 0.03 and 0.88 ± 0.03 s).. In conclusion, in young healthy female athletes, the Emotion showed better preservation of cardiopulmonary responses than the FFP2.
Keywords: Athletes; Cardiorespiratory fitness; Exercise test; Exercise tolerance; Female; Masks